MONITORING EFEK SAMPING PEMBERIAN FORMULA EKSTRAK DAUN LEGUNDI (Vitex trifolia L) DAN RIMPANG TEMULAWAK (Curcuma xanthorrhiza Roxb) PADA PENDERITA ALERGI RHINITIS - , Himaniarwati,S.Si,Apt, Prof. Dr. Zullies Ikawati, Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Temulawak and legundi has been scientifically shown to inhibit mast cell activation. Information undesirable side effects of legundi leaves and temulawak rhizome considered to be essential for development of the two materials into fitofarmaka anti-allergic preparation. The aim of this research is to determine the side effects of combination legundi leaf extract (Vitex trivolia L) and temulawak extract (Curcuma xanthorrhiza L) on allergic rhinitis patients. Observation of side effect used 33 subjects that divided into 3 groups namely the placebo group, treatment with the dose of 1500 mg / day treatment and the dose of 4500 mg/day. Blood chemical examinations performed before and after the treatment, observation of side effects symptoms performed 3 times daily for 14 days. Qualitative analysis carried out on observation of the organ systemby looking at the results of the side effects blank monitoring on the gastrointestinal system, central nervous system, respiratory system, cardiovascular system and organs of the skin. A quantitative analysis was also conducted statistical tests on organ systems and on blood chemical: physiology of the liver (SGPT and SGOT) and kidney physiology (kreatinine and BUN). The results of statistic test showed that no side effects on observation of systems gastrointestinal, central nervous, respiratory, cardiovascular and organs of the skin due to a combination of legundi leaf extract and temulawak extract in patients with allergic rhinitis on treatment of the dose of 1500 mg/day and 4500 mg/day. Similarly on the observation of physiological function of liver and kidney, no side effects occured on treatment with the dose of 1500 mg/day and 4500 mg/day for 14 days on patients with allergic rhinitis